Weight loss as a cause of superior mesenteric artery syndrome - Martins, Vânia Leitão; Cruz, António (BIRTH AND GROWTH MEDICAL JOURNAL, 2021)
Introduction and objective: Superior mesenteric artery syndrome (SMAS) is a rare condition in pediatric age, often presenting with non-specific gastrointestinal symptoms. The aim of this report was to highlight the importance of considering/excluding this diagnosis. Case description: A 17-year-old female presented with slowly progressing epigastralgia, heartburn, early satiety, nausea and sporadic vomiting with one and a half years of evolution. She had lost 13% of her weight in the previous six months. On physical examination, the girl complained of pain on epigastrium palpation, with no further changes. Laboratory tests were normal. Esophageal, gastric and duodenal transit (EGDT) revealed a vertically elongated stomach, with the greater curvature projecting towards the pelvic cavity and a slight delay in gastric emptying. Abdominal computed tomography scan confirmed the diagnosis of SMAS and a conservative approach with a hypercaloric fractionated diet was initiated. The girl maintained multidisciplinary follow-up (Nutrition, Pediatrics and Pedopsychiatry), with marked improvement and without requiring surgical intervention. Comments: Although rare, SMAS should be considered after exclusion of the most frequent underlying causes of persistent non-specific gastrointestinal symptoms.